The Harmonisation of Science and Religion: An Examination of Socio-Cultural Influences in Contemporary Islamic Contexts: Harmonisasi Sains dan Agama: Tinjauan Pengaruh Sosio-Kultural dalam Konteks Islam Kontemporer - Andini, Putri Khofifah Andini (Averroes: Journal for Science and Religious Studies, 2024)
This study aims to explore and identify the social, economic, political, and environmental factors influencing the relationship between science and religion in the contemporary Islamic world. Using a qualitative approach with case studies and in-depth interviews, this research examines various majority-Muslim countries with different socio-cultural backgrounds. The main findings indicate that integrating science and religion can improve the quality of life for Muslim communities through inclusive education, public policies oriented towards general welfare, and holistic approaches to environmental issues. This research makes a significant contribution to the academic literature on the relationship between science and religion and offers practical recommendations for policymakers, educators, and community leaders. The limitations of the study include its limited scope and potential bias inherent in qualitative methods. The conclusion emphasises the importance of ongoing efforts to harmoniously integrate science and religion to achieve sustainable development and societal well-being.